Planning and Designing the Convention Center in Sibolga City with a Neo-Vernacular Architectural Approach - Yulesta Putra (Talenta Publisher, 2023)
MICE is one of the drivers of tourism that can impact economic development in an area. Sibolga has the potential to become a MICE tourist destination because of its natural beauty, rich in historical and cultural heritage. However, the meeting facilities in Sibolga could not accommodate many people, thus requiring a convention center to accommodate the rapidly growing population without leaving any cultural characteristics there. A convention center is a place for people as usual groups (politicians, business people, scholars, and so on) can share knowledge and discuss a problem, new information, and interest. The design of this convention center aims to become a gathering center for visitors to seek information about things in Sibolga and its surroundings. In addition, the use of neo-vernacular architecture in the building is a manifestation of maintaining the traditional characteristics of Sibolga with a modern touch. The method uses the description method, which describes primary and secondary data with existing facts and then analyzes it to get conclusions. The design result is that the convention center, is expected to be a productive place to introduce and provide insight or knowledge. Attract local people and tourists to maintain and preserve the variety of arts and culture in Indonesia, especially in Sibolga.